Association between dispensing of low-value oral albuterol and removal from Medicaid preferred drug lists - Anna Volerman; Alison Pelczar; Rena Conti; Christina Ciaccio; Kao-Ping Chua (BMC, 2022)
Abstract Background Oral albuterol has worse efficacy and side effects compared with inhaled albuterol, and thus its use has been discouraged for decades. Drug inclusion or exclusion on formularies have been associated with reductions in low-value care. This study examines dispensing of oral albuterol and inclusion of oral albuterol on state Medicaid drug formularies--Preferred Drug Lists (PDLs). It also evaluates the association between removal of oral albuterol from the PDL and dispensing levels. Methods This quasi-experimental study determined oral albuterol inclusion on PDLs and dispensing between 2011 and 2018, using Medicaid program websites and the State Drug Utilization Database. Using a difference-in-differences model, we examine the association between removal of oral albuterol from Arkansas' Medicaid PDL in 2014 and dispensing of this drug through Medicaid, with Iowa as a control state. The outcome measure was the percent of all albuterol prescriptions that were for oral albuterol. Results A total of 28 state Medicaid PDLs included at least one formulation of oral albuterol in 2018. In 2018, 179,446 oral albuterol prescriptions were dispensed to Medicaid beneficiaries nationally. Medicaid programs paid approximately $3.0 million for oral albuterol prescriptions in 2018. Removal of oral albuterol syrup from the Arkansas PDL in March 2014 was associated with a more rapid decline in dispensing compared with Iowa which maintained this medication on their PDL. Conclusions Findings suggest that removal of low-value medications, such as oral albuterol, from PDLs may be one avenue by which state Medicaid programs can reduce wasteful spending while improving guideline-based care.